2006
DOI: 10.1177/10105395060180011101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time delay on survival in patients with non-small cell lung cancer — A Malaysian study

Abstract: The prognosis of lung cancer remains poor with overall five year survival figures varying between five and 10% worldwide, However, it has been shown that surgery in patients with early stage disease in non-small cell lung cancer can achieve five year survival rates up to 80%, suggesting that early or delay diagnosis can influence prognosis. Nevertheless, studies addressing this have been inconclusive and mostly derived from Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Eighteen studies examined the association between timeliness and one or more outcomes, including 15 studies that examined survival,6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 4 studies that examined stage distribution11 16 21 22 and 1 that examined tumour growth 23. Eight studies that described an intervention to improve timeliness of care were identified 24 25 26 27 28 29 30 31…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen studies examined the association between timeliness and one or more outcomes, including 15 studies that examined survival,6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 4 studies that examined stage distribution11 16 21 22 and 1 that examined tumour growth 23. Eight studies that described an intervention to improve timeliness of care were identified 24 25 26 27 28 29 30 31…”
Section: Resultsmentioning
confidence: 99%
“…Four Canadian studies21 34 35 36 and four Japanese studies12 15 16 37 were identified, including several studies that examined delays in care after mass population-based screening. We also included two studies from Turkey,17 38 one study from Australia24 and one study from Malaysia 9…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of patients receiving chemotherapy as their first treatment (alone or in combination with radiotherapy) ranged from 25 to 69%. No study demonstrated an association between TTC and survival among the entire meta‐analysis when considering TTC intervals from 30 days to 6 months or by per day analyses . One study did show improved survival with early TTC; however, this was observed only in the subgroup of patients with overall survival ≥5 years .…”
Section: Methodsmentioning
confidence: 98%
“…S5), 514 from MEDLINE, 72 from the Cochrane Library and an additional 12 papers identified from reference lists. Of these, 11 papers were reviewed. Studies varied by publication date (2000–2013) and size ( n = 21–10 583) and reported data for a heterogeneous group of patients (stages I–IV non‐small‐cell lung cancer (NSCLC) and limited‐ and extensive‐stage small‐cell lung cancer (SCLC)) as shown in Tables and .…”
Section: Methodsmentioning
confidence: 99%